Norges Bank's New Monetary Policy Loss Function - Further Discussion - Snorre Evjen; Thea Birkeland Kloster (Norges Bank, 2012)
Norges Bank's Monetary Policy Report (MPR) 1/12 introduced amendments to the criteria for an appropriate interest rate path in order to explicitly take into account the risk of a buildup of financial imbalances. The monetary policy "loss function" used in model-based analyses was accordingly adjusted mainly in two ways: The weight on the output gap was increased and a weight on the deviation between the actual and the normal interest rates was added. We present both theoretical and empirical studies underpinning these changes.
hdl:11250/2507191
Keywords: 330